1998
DOI: 10.1001/jama.280.1.42
|View full text |Cite
|
Sign up to set email alerts
|

New Testing Strategy to Detect Early HIV-1 Infection for Use in Incidence Estimates and for Clinical and Prevention Purposes

Abstract: Context.-Differentiating individuals with early human immunodeficiency virus 1 (HIV-1) infection from those infected for longer periods is difficult but important for estimating HIV incidence and for purposes of clinical care and prevention.Objective.-To develop and validate a serologic testing algorithm in which HIV-1-positive persons with reactive test results on a sensitive HIV-1 enzyme immunoassay (EIA) but nonreactive results on a less sensitive (LS) EIA are identified as having early infection.Design.-Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
491
1
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 631 publications
(503 citation statements)
references
References 48 publications
8
491
1
3
Order By: Relevance
“…Participants from SCOPE were selected based on a history of strong HIV-specific CD4 + T cell IFN-γ secretion (Emu et al, 2005), including those in three categories: (1) long-term nonprogressor (LTNP) who have been infected at least 10 years with a viral load <5000 RNA copies/ml without antiretroviral therapy, (2) "elite" controllers who have an undetectable viral load (<75 RNA copies/ml) without antiretroviral therapy, and (3) progressors who have higher viral loads (> 10,000 RNA copies/ml) and CD4 counts <500 cells/ml. Participants selected from the Options cohort were in primary HIV infection, determined by a negative HIV antibody or detuned antibody test (Janssen et al, 1998), a high viral load and a normal CD4 count, and were within 12-50 days from the onset of symptoms at their screening visit. STI subjects with a range of CD4 + T cell responses to Gag, Towne CMV vaccine recipients and healthy uninfected donors with a range of responses to CMV pp65 were selected.…”
Section: Study Subjectsmentioning
confidence: 99%
“…Participants from SCOPE were selected based on a history of strong HIV-specific CD4 + T cell IFN-γ secretion (Emu et al, 2005), including those in three categories: (1) long-term nonprogressor (LTNP) who have been infected at least 10 years with a viral load <5000 RNA copies/ml without antiretroviral therapy, (2) "elite" controllers who have an undetectable viral load (<75 RNA copies/ml) without antiretroviral therapy, and (3) progressors who have higher viral loads (> 10,000 RNA copies/ml) and CD4 counts <500 cells/ml. Participants selected from the Options cohort were in primary HIV infection, determined by a negative HIV antibody or detuned antibody test (Janssen et al, 1998), a high viral load and a normal CD4 count, and were within 12-50 days from the onset of symptoms at their screening visit. STI subjects with a range of CD4 + T cell responses to Gag, Towne CMV vaccine recipients and healthy uninfected donors with a range of responses to CMV pp65 were selected.…”
Section: Study Subjectsmentioning
confidence: 99%
“…The development of new methods for basing incidence estimates on cross-sectional samples (without the need for follow-up) will allow much closer monitoring of incidence in high-risk populations, including IDUs. 30 …”
Section: Discussionmentioning
confidence: 99%
“…The same specimens were tested in the three A11 less sensitive (LS/detuned)-EIA protocol as described. 8,9 Results are interpreted based on the standardized OD (SOD) of test samples, which is derived by dividing the mean OD of test sample on the LS-EIA by the mean OD of the CDC supplied assay Calibrator (Cal). Total plasma IgG quantification was performed by single radial immunodiffusion assay using commercially available kits according to the manufacturer's recommended protocol (The Binding Site, San Diego, CA, USA).…”
Section: Cdr3 B Cell Spectratyping In Early Hiv Mk Elkins Et Almentioning
confidence: 99%
“…Analysis was based on IgG heavy chain gene utilization and CDR3 length measurement (spectratyping), 7 and relationship with CD4/CD8 counts, viral load, and serologic responses. Individuals with acute or recent HIV-1 infection were eligible for this study if the initial evaluation indicated that they met one or more of the criteria for recent HIV-1 infection: (1) detectable HIV-1 RNA in blood plasma and a negative or indeterminate Western blot assay for anti-HIV-1 antibodies; (2) a positive enzyme-linked immunosorbent assay (ELISA) with Western blot confirmation within 12 months of a documented negative HIV-1 antibody test; or (3) a sensitive/less sensitive (S/LS) dual ELISA testing optical density ratio of less than 0.75 8,9 with a history compatible with recent HIV infection. 10 The dual enzyme immunoassay (EIA) testing strategy using a standard high sensitivity EIA and an LS EIA takes advantage of the progressive development of HIV antibody response during the initial phase of infection.…”
mentioning
confidence: 99%